Banks in Disadvantaged Areas - Johann Burgstaller (Kredit und Kapital, 2012)
Banks in Disadvantaged Areas Based on the presumption that the empirical banking literature devotes too little attention to institutions with special features, this paper examines banks that are affected by low regional development. Data on the full population of Austrian banks is applied to identify such banks and to study their particular characteristics. It turns out that banks operating in disadvantaged areas differ from their counterparts with respect to individual as well as market–related attributes. Additionally, several effects commonly estimated in empirical banking models prove to be sensitive to the exclusion of these institutions from the estimation sample. These comprise the effect of bank size on the net interest margin, the heterogeneity of loan supply reactions to monetary policy signals which are related to the banks' liquidity position, and the influence of local concentration on competitive behavior. Our findings confirm that key empirical results may be driven by certain groups of banks with special features. Thus, support is provided for the necessity of a more critical view of empirical outcomes for "the average bank", both from national samples and cross–country studies. (JEL G21, L11, R32) – – Banken in strukturschwachen Regionen Vor dem Hintergrund, dass empirische Literatur oft zu wenig Augenmerk auf die Heterogenität von Finanzinstitutionen legt, untersucht diese Arbeit Banken in strukturschwachen Räumen. Daten für die Gesamtheit der österreichischen Banken werden herangezogen, um solche Institute zu identifizieren und um ihre speziellen Charakteristiken zu beleuchten. Dabei zeigt sich, dass sich Banken, die von einer schwachen Regionalentwicklung betroffen sind, in vielen Attributen signifikant vom Rest der Kreditinstitute unterscheiden. Zusätzlich kann beobachtet werden, dass sich die Resultate für oftmals in der Bankenliteratur bemühte Zusammenhänge verändern, wenn diese Banken aus der Datenbasis entfernt werden. Dies ist im konkreten Fall zutreffend für den Einfluss der Bankengröße auf die Nettozinsmarge, für die Reaktion der Kreditvergabe auf geldpolitische Impulse in Abhängigkeit von der Liquiditätssituation und für den Effekt von Konzentration in lokalen Märkten auf das Wettbewerbsverhalten. Die Ergebnisse dieser Arbeit lassen vermuten, dass manch empirisches Resultat auf gewisse Bankengruppen mit bestimmten Eigenschaften zurückführbar ist. Daher sollten darauf basierende Aussagen, die "die durchschnittliche Bank" betreffen, kritischer unter die Lupe genommen werden.
Keywords: G21; L11; R32; 330